Genoese Entrepreneurship and the Asiento Slave Trade, 1650-1700 (Taylor & Francis, 2022)
1650-1700, Asiento, Entrepreneurship, Genoese, Slave, Trade
English
Keywords: History of the Americas; 1650-1700, Asiento, Entrepreneurship, Genoese, Slave, Trade